A 96‐week, double‐blind, randomized controlled trial comparing bexagliflozin to glimepiride as an adjunct to metformin for the treatment of type 2 diabetes in adults. Issue 1 (23rd October 2022) - Halvorsen, Yuan‐Di; Lock, John Paul; Frias, Juan P.; Tinahones, Francisco José; Dahl, Dominik; Conery, Annie L.; Freeman, Mason W.
Abstract: Aim: To compare the effects of bexagliflozin tablets 20 mg, with those of optimally titrated glimepiride when used to treat adults with type 2 diabetes mellitus (T2DM) inadequately controlled by metformin. Methods: Adults with type 2 diabetes (n = 426) taking metformin, and with a glycated haemoglobin (HbA1c) level between 53 and 91 mmol/mol [7.0% and 10.5%], were randomized to receive bexagliflozin tablets 20 mg or titrated glimepiride. The primary endpoint was the intergroup difference in the change from baseline to Week 60 in percent HbA1c. Secondary endpoints included changes from baseline in body mass and systolic blood pressure (SBP), and proportion of subjects experiencing severe or documented symptomatic hypoglycaemia. Results: The intergroup difference in percent HbA1c (bexagliflozin minus glimepiride) from baseline to Week 60 was −0.55 mmol/mol (95% confidence interval [CI] –2.30, 1.20)‐[−0.05% (−0.21, 0.11)], establishing noninferiority of bexagliflozin to glimepiride by the prespecified margin of 3.83 mmol/mol [0.35%]. Prespecified tests gave, in order, a difference in body mass of −4.31 kg (95% CI −5.10, −3.52; P  < 0.0001), a difference in SBP of −6.53 mm Hg (95% CI −10.56, −2.51; P  = 0.0008), and an odds ratio of 0.12 (95% CI 0.05, 0.28; P  < 0.0001) for severe or documented symptomatic hypoglycaemia. At the follow‐up visit the mean difference in estimated glomerular filtration rate (eGFR) between arms was 6.05 mL min −1 per 1.73 m 2 (95% CI, 3.24, 8.87; P  < 0.0001). Conclusions: Bexagliflozin was noninferior to glimepiride in lowering HbA1c, was superior to glimepiride for decreases in body mass and SBP, and was associated with significantly fewer hypoglycaemic events than glimepiride. A favourable effect on eGFR was observed.